Surging Energy Prices in Europe in the Aftermath of the War : How to Support the Vulnerable and Speed up the Transition Away from Fossil Fuels - Ari, Anil (IMF Working Papers; Working Paper, 2022)
We estimate that the recent surge in international fossil fuel prices will raise European households' cost of living in 2022 by close to 7 percent of consumption on average. Household burdens vary significantly across and within countries, but in most cases they are regressive. Policymakers have mostly responded to the shock with broad-based price-suppressing measures, including subsidies, tax reductions, and price controls. Going forward, the policy emphasis should shift rapidly towards allowing price signals to operate more freely and providing income relief to the vulnerable. The surge in energy prices will encourage energy conservation and investments in renewable energy, but the manyfold rise in natural gas prices could lead to a persistent switch towards coal. To ensure steady progress towards carbon emissions reduction goals, authorities could use the opportunity to strengthen carbon pricing when global fossil fuel prices decline in the future. Non-price incentives for investments in energy efficiency and renewable energy should also be enhanced, as envisaged in the RePowerEU plan.